Disentangling the Effects of Nonmetro Location and Student Poverty on School Performance/Improvement: Implications for Equitable Excellence in Kentucky Public Schools - Edward B. Reeves (Journal of Research in Rural Education, 2003)
Kentuckt public schools face a daunting challenge in meeting the state's proficiency standard by 2014. The present study evaluates the effects of student poverty and location on school accountability scores. Long-term as well as short- term models of these effects are examined using a sample of 1,115 schoold nested in 171 school district. Short-term effects are estimated with hirarchical linear modeling. The HLM results are then used to etimate how schools with hypothetical characteristicts will be performing in 2014. The HLM analysis fids that student poverty has a negative effect on the baseline school performance, and this effect is greater than that of location. The effects of location, on the other hand, are most aparent in the annual change in scores. A positive effect is associated with most nonmetro locations. These findings disclose a rural school advantage that does not lie in small schools and small districts alone. The long-term projections show poverty and location each influencing the outcomes, although the positive effect of nonmetro location does not erase the strongly negative effect of poverty. If the projections are realized, equitable excellence will not be achieved in Kentucky public schools during the foreseable future. The paper discussing remedies for inequity and policy options for warding off the projected outcome of large numbers of public schools failing to achieve proficiency.